ANALISIS RISIKO PADA TAHAP PELAKSANAAN KONSTRUKSI JALAN TOL CINERE – JAGORAWI, DEPOK - Muhammad Faisal (Jurnal Proyek Teknik Sipil, 2021)
Cinere-Jagorawi Toll Road is a part of Jakarta Outer Ring Road (JORR) II which has the total length of 110 kilometer that circle around Seokarta-Hatta International Airport until Tanjung Priok. By the existance of JORR II, there would be an easy access from seaport to airport and vice versa. This also would be streamlining traffic flow from west to east considering the traffic at JORR I has overused which could cause congestion.  In every construction of the Toll Road, there would be some risks that possibly arise.  To minimize the risks that could occur, identification, anlysis, mitigation and allocation towards the possible risks – especially the risks which are classified in dominant category - are essential. This is expected to be a basis of decision making by stakeolders to resolve negative consequences that happen during the construction of Toll Road. In this research, the researcher uses qualititive descriptive research with survey method using questionnaire as a research instrument. According to the result of questionnaire, there were 45 risks identified in this research. After acquiring the result from questionnaire, the next step were determining validity and reliability, and analysing the acceptance of the risks to identify which risks are classified as domminant risks factor. There were 8 (18%) risks classified as Unacceptable Category and 37 (82%) risks classified as Undesireble Category.  The next step was mitigating the risks included in domminant risk factors. Based on risk mitigation, ownership risk management should be carried out by the stakeholeders involved in Toll Road construction.